Avanços da democracia? parcerias entre Estado e Sociedade Civil no Brasil do pré- golpe: a percepção dos agentes públicos do governo federal e o novo Marco Regulatório das Organizações da Sociedade Civil - Schwarz, Letícia (2017)
This dissertation aims to analyze the perception of federal managers on possible advances and achievements in the relations between State and Society in Brazil in the context that precedes the approval of the new Regulatory Framework of Civil Society Organizations, MROSC (Law 13,019 / 2014). The hypothesis is that the cycle of expansion of social policies -that Brazil observed from 2003 to 2015 -- was accompanied by models of policy implementation that included Civil Society Organizations (CSOs) as key agents. These implementation models, in turn, are associated with a set of values expressed by a category of middle managers, not necessarily organized, henceforth called activist managers (ABERS, 2015). They work in various institutions in the federal public administration, and presented varying degrees of commitment to the implementation of policies through CSOs, generating evidence of state recognition of an area crucial to the implementation of state policies, especially those in social, human rights and minority fields. The confirmation that the State has become more permeable to Civil Society Organizations is based on the verification of narratives about the partnerships for the implementation of policies, practices to simplify these partnerships and the narrative expressed by Law 13,019 / 2014, which established specific legal regime for such partnerships.